(untitled) (The Review of Diabetic Studies, 2025)
Background: Emergency and critical care settings represent the most demanding environments within healthcare systems, requiring sophisticated strategic health management to ensure nursing excellence, operational efficiency, and optimal patient outcomes. The integration of evidence-based management strategies has become increasingly vital as healthcare systems face escalating demands, workforce shortages, and complex patient presentations. Objectives: This systematic review aimed to synthesize evidence on the impact of strategic health management approaches on nursing excellence in emergency and critical care settings, specifically examining operational outcomes, quality standards implementation, and community health education initiatives. Methods: A comprehensive search of PubMed, Embase, CINAHL, Cochrane Library, and Web of Science was conducted from January 2020 to March 2026. Studies examining strategic health management interventions in emergency departments (EDs) and intensive care units (ICUs) were included. Data extraction encompassed study design, setting, strategic management focus, interventions, outcomes, and quality assessment. The Mixed Methods Appraisal Tool (MMAT) and adapted quality criteria were used for methodological evaluation. Results: Ten studies met inclusion criteria, comprising systematic reviews, scoping reviews, cross-sectional surveys, and meta-analyses. Strategic interventions demonstrated significant improvements across operational outcomes (ED length of stay reduction: 35%, triage accuracy improvement: 28%), quality standards (mortality reduction: 14%, infection prevention: 20%), and workforce outcomes (patient satisfaction: +18%, nurse satisfaction: +22%). Key strategic domains included workforce management, technology integration, quality improvement frameworks, and community disaster preparedness education. Conclusion: Strategic health management significantly enhances nursing excellence across operational, quality, and educational dimensions. Evidence supports the implementation of comprehensive approaches integrating workforce optimization, technology-enhanced care delivery, standardized quality indicators, and community health education to achieve sustainable improvements in emergency and critical care nursing.